New ways of seeing Picasso, Braque and the cubist revolution (Home Vision [distributor], 1898)
Documents the extraordinary exhibition mounted by the Museum of Modern Art and presents a rare and provocative view of cubism and the inspired collaboration of Picasso and Braque.